Eccentric and concentric exercise of the triceps surae: An in vivo study of dynamic muscle and tendon biomechanical parameters - Chaudhry, S.; Morrissey, D.; Woledge, R. C.; Bader, D. L.; Screen, H. R. C. (Journal of Applied Biomechanics, 2015)
Triceps surae eccentric exercise is more effective than concentric exercise for treating Achilles tendinopathy, however the mechanisms underpinning these effects are unclear. This study compared the biomechanical characteristics of eccentric and concentric exercises to identify differences in the tendon load response. Eleven healthy volunteers performed eccentric and concentric exercises on a force plate, with ultrasonography, motion tracking, and EMG applied to measure Achilles tendon force, lower limb movement, and leg muscle activation. Tendon length was ultrasonographically tracked and quantified using a novel algorithm. The Fourier transform of the ground reaction force was also calculated to investigate for tremor, or perturbations. Tendon stiffness and extension did not vary between exercise types (P = .43). However, tendon perturbations were significantly higher during eccentric than concentric exercises (25%-40% higher, P = .02). Furthermore, perturbations during eccentric exercises were found to be negatively correlated with the tendon stiffness (R2 = .59). The particular efficacy of eccentric exercise does not appear to result from variation in tendon stiffness or extension within a given session. However, varied perturbation magnitude may have a role in mediating the observed clinical effects. This property is subject-specific, with the source and clinical timecourse of such perturbations requiring further research.